Pteropus vampyrus TRIM40 Is an Interferon-Stimulated Gene That Antagonizes RIG-I-like Receptors - Sarah van Tol; Adam Hage; Ricardo Rajsbaum; Alexander N. Freiberg (Viruses, 2023)
Nipah virus (NiV; genus: Henipavirus; family: Paramyxoviridae) naturally infects Old World fruit bats (family Pteropodidae) without causing overt disease. Conversely, NiV infection in humans and other mammals can be lethal. Comparing bat antiviral responses with those of humans may illuminate the mechanisms that facilitate bats’ tolerance. Tripartite motif proteins (TRIMs), a large family of E3-ubiquitin ligases, fine-tune innate antiviral immune responses, and two human TRIMs interact with Henipavirus proteins. We hypothesize that NiV infection induces the expression of an immunosuppressive TRIM in bat, but not human cells, to promote tolerance. Here, we show that TRIM40 is an interferon-stimulated gene (ISG) in pteropodid but not human cells. Knockdown of bat TRIM40 increases gene expression of IFNβ, ISGs, and pro-inflammatory cytokines following poly(I:C) transfection. In Pteropus vampyrus, but not human cells, NiV induces TRIM40 expression within 16 h after infection, and knockdown of TRIM40 correlates with reduced NiV titers as compared to control cells. Bats may have evolved to express TRIM40 in response to viral infections to control immunopathogenesis.